Doses of organic substrate in the production of red chili pepper seedlings - Costa, Francisco Cleilson Lopes; Silva, Regimara Francisca Bernardo da; Silveira, Antônia Thalyta Lopes; Uchôa, Keline Sousa Albuquerque; Deus, Maria Vanessa da Costa de; Silva, Maria Monica da (Revista Internacional de Ciências, 2017)
Organic matter influences the plant performance, mainly on early stages of the plant development. The aim of this work was to assess manure doses influence on the germination potential of red pepper seeds. The research was carried out in greenhouse at Unidade Experimental de Pesquisa e Extensão (UEPE) of Instituto Federal do Ceará, located in Chapada do Apodi, Limoeiro do Norte - Ceará, geographic coordinates 5°10’ S, 38°00’ W, and altitude of 145,9 m. The experimental design was completely randomized, the treatments were composed by manure (M) and soil proportions (S) (%): 0M-100S, 25M-75S, 50M-50S, 75M-25S and 100M-0S, respectively. The variables assessed were Emergence Speed Index (ESI), Viability Rate (%VR), Post-Emergence Rate of Abortion (%PEA), Global Germination (%GG), Seedling Height (SH) (cm), Root Depth (RD) (cm), Aerial Length (AL) (cm), Number of Leaves (NL), Fresh Weight (FW) (g) and Dry Weight (DW) (g).